Influence of model inclination on the melting behavior of graded metal foam composite phase change material: A pore-scale study. (15th December 2021) - Li, Hongyang; Hu, Chengzhi; He, Yichuan; Tang, Dawei; Wang, Kuiming; Hu, Xianfeng
Highlights: l The melting of the metal foam composite PCM is studied in pore-scale. l The effect of the heat flux orientation on the melting is studied. l The effect of the gradient porosity of metal foam is clarified. l The whole melting performance is analyzed. Abstract: Metal foam has been widely employed to accelerate the melting behavior of latent heat thermal energy storage (LHTES) system. Nevertheless, its homogeneous structure has a limited enhancement on the conductive and convective heat transfers in the melting process. In this study, we numerically studied the heat storage performance of the graded metal foam composite phase change materials (CPCMs). The body-centered-cubic unit was conducted to represent the metal foam with a complex interconnected structure. For clarifying the effect of heat flux orientation, we built seven models with the inclinations of 0˚, 30˚, 60˚, 90˚, 120˚, 150˚, 180˚, respectively. Meanwhile, three types of metal foams with different structures, including the uniform, negative, and positive porosities, were built to enhance the melting process and analyze their effects. By comparing the melting performances of the uniform models with different inclinations, it is found that the heat flux orientations (model inclinations) have significant impacts on the melting behaviors. The models with large inclinations ( θ > 90˚) have faster melting-processes compared with those small inclinations ( θ ≤ 90˚). Besides, by comparing the models with different graded structures, we conclude that the negative model is the most helpful to the charging process. When the inclinations of the models are 120˚ and 150˚, the negative models have reductions of 11.06% on the complete melting times compared with those uniform models. Nevertheless, the models with small inclinations were slightly enhanced by negative porosity structure (0.52%–3.15%) but significantly weakened by positive structure (21.93%–30.00%). The study reveals the effects of heat flux orientation and graded metal foam on the melting performance of PCM. It provides a design and optimized reference for the models with tilted angles such as electronic devices and plate latent heat storage systems. Graphical abstract: Image, graphical abstract .